The ability of Arabidopsis to recover from Basta and its application in isolating Cas9-free mutants - Ahmed, Shahbaz; Hulbert, Anna K.; Xin, Xin; Neff, Michael M. (Frontiers in Plant Science, 2024)
After successfully performing Agrobacterium-mediated CRISPR-Cas9-based gene editing in plants, isolation of the Cas9 T-DNA is essential for the stable inheritance of induced mutations. Here, we report a simple technique that allows the isolation of Cas9-free mutants, eliminating the need for outcrossing or other intricate methods. This method is based on the ability of Basta-sensitive Arabidopsis thaliana seedlings, which generally perish, to recover and grow once transplanted to Basta-free growth media. By growing gene-edited heterozygous populations of single-locus insertion Basta-resistant plants on Basta selection media, plants lacking the Cas9 T-DNA can be identified. These pale-looking plants lacking Cas9 are then rescued on media lacking the Basta to recover Cas9-free plants. The ability of seedlings to recover from Basta selection was also studied in camelina, canola, and wheat. All three crops showed different recovery rates, with wheat demonstrating the highest recovery once transplanted from Basta to normal growth media. In summary, our findings demonstrate that by harnessing the recovery capability of Basta-sensitive seedlings, we can effectively identify and rescue plants lacking the Cas9 T-DNA, enabling the isolation of Cas9-free mutants in Arabidopsis and potentially extending to other crops.